Impact of posttranslational modifications of engineered cysteines on the substituted cysteine accessibility method: evidence for glutathionylation - Zhao, Rongbao (Am J Physiol Cell Physiol, 2017)
The substituted cysteine accessibility method (SCAM) is widely used to study the structure and function of channels, receptors and transporters. In its usual application, a cysteine residue is introduced into a protein which lacks native cysteines following which the accessibility of the residue to the aqueous compartment is assessed. Implicit, and generally assumed, is that if the cysteine-substituted residue is not available to react with sulfhydryl reagents it is not exposed to the extracellular compartment or within the aqueous translocation pathway. We demonstrate here, in a Hela-derived cell line, that some cysteine-substituted residues of the proton-coupled folate transporter (PCFT, SLC46A1) that are inaccessible to 2-((biotinoyl)amino)ethyl methanethiosulfonate are glutathionylated by biotinylated glutathione ethyl ester in the absence of an oxidizing agent. Intramolecular disulfide formation involving cysteine-substituted residues was also identified in some instances. These posttranslational modifications limit the accessibility of the cysteine residues to sulfhydryl-reactive reagents and can have a profound impact on the interpretation of SCAM but may not alter function. When a posttranslationally modified residue is used as a reference extracellular control, the high level of exposure required for detection on Western blot results in erroneous detection of otherwise inaccessible intracellular cysteine-substituted residues. The data indicate that in the application of SCAM, when a cysteine-substituted residue does not appear to be accessible to sulfhydryl-reactive reagents, the possibility of a posttranslational modification should be excluded. The data explain the discrepancies in the assessment, and confirm the localization, of the first intracellular loop of PCFT.